Preparation method of polyester fiber and preparation method of catalyst

By using materials such as zinc oxide and sulfur sources in the preparation of polyester fibers, combined with in-situ polymerization and melt spinning processes, the safety hazards, high costs and pollution problems of existing antibacterial and anti-ultraviolet functional materials are solved, and high value-added and environmentally friendly anti-bacterial and anti-ultraviolet functions are achieved.

CN119640432AActive Publication Date: 2025-03-18JIANGSU RUIBANG TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510167721.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-03-18
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

Existing antibacterial and UV-resistant functional materials have safety hazards, high costs, pollution problems and poor washing resistance, making it difficult to meet high value-added and environmental protection requirements.

Method used

Using a preparation method of polyester fiber, by dissolving zinc oxide and sulfur sources in a mixed solvent of ethylenediamine and ethanolamine, adding organic acids and iron-containing compounds, the reaction is obtained to obtain a functional powder, and antibacterial and ultraviolet-resistant polyester fibers are prepared by in-situ polymerization and melt spinning processes.

Benefits of technology

The prepared polyester fiber has the dual functions of decomposing formaldehyde, antibacterial and ultraviolet resistance. It is safe and non-toxic, cost-effective, lower than traditional methods, and reduces pollution and meets high value-added and environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640432A_ABST
    Figure CN119640432A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a polyester fiber and a preparation method of a catalyst, the preparation method of the polyester fiber comprises the following steps: (1) dissolving zinc oxide and a sulfur source in a mixed solvent of ethanediamine and ethanolamine, then adding an organic acid and an iron-containing compound, and reacting to obtain functional powder, the reaction temperature is controlled to be 180-220 DEG C during the reaction; and (2) mixing the functional powder obtained in the step (1) with a polyester raw material, carrying out an in-situ polymerization reaction to obtain a functional polyester chip, and carrying out melt spinning to obtain the polyester fiber. The polyester fiber prepared through the preparation method of the polyester fiber achieves the function of ultraviolet absorption and visible light emission through photon down-conversion, the requirement of a human body for visible light can be compensated, and the fabric woven from the polyester fiber has the function of decomposing formaldehyde, acetaldehyde and propionaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyester production, and specifically relates to a method for preparing polyester fiber and a method for preparing a catalyst. Background Art

[0002] Antibacterial and anti-ultraviolet functional materials have always been an important product in the functional development of chemical fiber fabrics and an important direction for the application and development of outdoor fabric products. At present, there are some solutions, such as solving the problem from the origin of the fiber, which can prepare antibacterial and anti-ultraviolet fibers, such as using high addition and composite spinning technology to prepare antibacterial and anti-ultraviolet functional fibers, using nano zinc oxide, titanium dioxide or rare earth as functional additives to obtain functional fibers by melt spinning, and fabrics prepared with these fibers can meet the antibacterial and anti-ultraviolet requirements of fabrics, but such fibers also have irreparable defects as follows: First, the use of rare earth powders has the risk of radiation, and some rare earths are biologically toxic, and there are safety hazards in their use; second, the simple addition of zinc, silver and titanium dioxide to obtain antibacterial and anti-ultraviolet functions, high zinc addition affects spinning performance, and silver addition has high cost.

[0003] At present, most fabrics on the market use antibacterial and anti-ultraviolet finishing to achieve the functions of the fabrics. For example, organic antibacterial agents such as quaternary ammonium salts are used in combination with anti-ultraviolet additives. This method is relatively low-cost and has significant effects compared to the use of antibacterial and anti-ultraviolet functional fibers. However, although this method is cheap and effective, it also has inevitable defects: (1) Additional pollution. At present, antibacterial and anti-ultraviolet additives are generally used for finishing, which increases the degree of wastewater pollution and increases the difficulty of wastewater treatment; (2) Insufficient durability. The antibacterial and anti-ultraviolet functional finishing methods currently used have poor wash resistance. Generally, few can meet the wash resistance requirements of the standards, which is not conducive to the export of textiles, reduces the competitive advantage of textiles, and increases trade disputes.

[0004] The antibacterial and anti-UV functional materials currently on the market cannot remove formaldehyde, have low added value, and some fabrics contain heavy metal elements, posing a safety hazard. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing polyester fiber and a method for preparing a catalyst. The prepared polyester fiber can decompose formaldehyde, is antibacterial and anti-ultraviolet, is safe and non-toxic, and has a high cost-effectiveness.

[0006] In order to achieve the above object, a technical solution adopted by the present invention is: A method for preparing polyester fiber, comprising: (1) first dissolving zinc oxide and a sulfur source in a mixed solvent of ethylenediamine and ethanolamine, then adding an organic acid and an iron-containing compound to react to obtain a functional powder, wherein the iron in the iron-containing compound is trivalent iron, and the reaction temperature is controlled to be 180-220° C. during the reaction; (2) The functional powder of step (1) is mixed with polyester raw material to carry out in-situ polymerization reaction to obtain functional polyester chips, which are then melt-spun to obtain polyester fibers.

[0007] According to some implementation aspects of the present invention, in step (1), the sulfur source includes sulfur powder.

[0008] According to some embodiments of the present invention, in step (1), the iron-containing compound is a combination of one or more selected from ferric chloride or ferric sulfate.

[0009] According to a preferred embodiment of the present invention, in step (1), the iron-containing compound is ferric chloride hexahydrate. After the iron ions in the ferric chloride hexahydrate are dissociated during the reaction, the hydrochloric acid can exist in a gaseous state under high temperature and high pressure conditions.

[0010] According to some implementation aspects of the present invention, in step (1), the amount of the iron-containing compound added is 0.2-2% of the sum of the mass of the zinc oxide and the sulfur source.

[0011] According to some embodiments of the present invention, in step (1), the organic acid is a combination of one or more selected from oxalic acid and acetic acid; and the mixed solution of the organic acid and the iron-containing compound is neutral or weakly acidic.

[0012] According to a preferred embodiment of the present invention, in step (1), the organic acid is oxalic acid.

[0013] Since amine substances are used in the preparation, it is known that amine substances (functional powder surface contains amino groups) will attack the ester bonds in polyester to break them, resulting in a decrease in polymerization degree, which will accelerate the degradation of polyester polymers during later processing and use. Therefore, organic acids are added to the solvent, and the organic acids react with the -NH groups in the amine substances to produce amide bonds. The functional powder dissolution pH is adjusted to neutral or weakly acidic to improve the compatibility with polyester resins and mechanical properties.

[0014] According to some implementation aspects of the present invention, the amount of the organic acid added is 0.05-0.2% of the sum of the mass of the zinc oxide and the sulfur source.

[0015] According to some implementation aspects of the present invention, in step (1), the mixed solvent of ethylenediamine and ethanolamine is conducive to the synthesis of zinc sulfide (ZnS) without producing side reactions.

[0016] According to a preferred embodiment of the present invention, in step (1), the mass ratio of ethylenediamine to ethanolamine is (1:2)-(2:1), preferably, the mass ratio of ethylenediamine to ethanolamine is 1:1.

[0017] According to some implementation aspects of the present invention, in step (1), the mass fraction of the zinc oxide and the sulfur source dissolved in the mixed solvent of ethylenediamine and ethanolamine is 5-25%.

[0018] According to some embodiments of the present invention, in step (1), zinc oxide and a sulfur source are dissolved in a mixed solvent of ethylenediamine and ethanolamine in a certain proportion, a certain amount of organic acid is added to the mixed solvent, the mixture is magnetically stirred, and then an iron-containing compound is added to the mixture, the mixture is stirred, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and stirring is continued; after sealing, the autoclave is heated to 180-220°C and maintained at this temperature for 12-36 hours, and then naturally cooled to room temperature; the precipitate is collected, washed several times with anhydrous ethanol and deionized water, and finally dried in a vacuum oven at a drying temperature of 50-100°C and a drying time of 5-8 hours.

[0019] According to a preferred embodiment of the present invention, in step (1), the product is dried in a vacuum oven at 60° C. for 6 hours.

[0020] According to a preferred embodiment of the present invention, in step (1), the reaction temperature is controlled to be 180-200°C.

[0021] According to a preferred embodiment of the present invention, in step (1), the pressure in the autoclave is 1-7.5 atmospheres.

[0022] According to some embodiments of the present invention, in step (2), the polyester raw material includes polyols and polyacids. The functional powder prepared in step (1) is first prepared into nanopowders by liquid grinding and dispersed in a polyol medium. Titanates are then added as surface modifiers and dispersants to improve their dispersibility to obtain a blend. The blend is then in-situ polymerized with the polyols and polyacids to obtain functional polyester chips.

[0023] According to some embodiments of the present invention, in step (2), the polyol includes ethylene glycol; the grinding is performed using a liquid phase ball mill, the grinding time is 6-12 hours, the particle size of the functional powder after grinding is 3-30 nm, and the mass fraction of the functional powder is 5-20%; and the amount of titanate surface modifier added is 1-3% of the powder mass.

[0024] According to a preferred embodiment of the present invention, in step (2), the particle size of the functional powder after grinding is less than 10 nm.

[0025] According to some implementation aspects of the present invention, in step (2), the in-situ polymerization includes: first mixing the blend with ethylene glycol, and then in-situ polymerizing it with terephthalic acid to obtain a functional polyester chip, wherein ethylene glycol and terephthalic acid are used as polymerization monomers and nano-titanium dioxide is used as a catalyst for catalytic polymerization.

[0026] According to some embodiments of the present invention, in step (2), the polymerization is divided into prepolymerization, post-condensation polymerization and final polymerization, the prepolymerization temperature is 170-200°C, and the time is 40-80 min; the post-condensation temperature is 230-270°C, and the time is 1-3 h; the final polymerization temperature is 260-290°C, and the time is 1-4 h.

[0027] According to some embodiments of the present invention, in step (2), the molar ratio of ethylene glycol (a mixture of ethylene glycol and the blend) mixed with the blend to terephthalic acid is (1-1.2):1.

[0028] According to some implementation aspects of the present invention, in step (2), the mass fraction of the functional powder in the polyester chips is 0.1%-2%, preferably 0.1-1.6%.

[0029] According to some embodiments of the present invention, in step (2), the polyester chips are dried and then fed into the feeder of the spinning machine for melt spinning, the spinning temperature is 260-300°C, the spinning speed is 600-3000m / min, and the initial pressure of the spinning assembly is 8-16MPa.

[0030] According to some embodiments of the present invention, in step (2), the spinning temperature is 285° C. and the spinning speed is 2800 m / min.

[0031] According to some implementation aspects of the present invention, in step (2), the molecular weight of the functional polyester chips is 20,000-30,000.

[0032] According to some embodiments of the present invention, in step (2), the molecular weight of the functional polyester chips is 23,000-26,000.

[0033] According to some embodiments of the present invention, in step (2), white / light-colored polyester fibers are prepared; the single fiber fineness of the polyester fibers is 0.5-5D.

[0034] Another technical solution adopted by the present invention is: A method for preparing a catalyst comprises: first dissolving zinc oxide and a sulfur source in ethylenediamine, ethanolamine and a mixed solvent, then adding an organic acid and an iron-containing compound, reacting to obtain a functional powder, wherein the iron in the iron-containing compound is trivalent iron, and the reaction temperature is controlled to be 180-220°C during the reaction.

[0035] Another technical solution adopted by the present invention is: The catalyst prepared by the catalyst preparation method is applied to the preparation of polyester fibers.

[0036] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: The preparation method of the polyester fiber of the invention comprises the following steps: firstly obtaining iron-doped zinc sulfide nano-functional powder, wherein iron exists in the form of surface modification groups on the surface of the nano-material, wherein zinc sulfide can shield ultraviolet rays, and iron has an antibacterial function; the surface of the functional powder contains amino groups (NH groups), and organic acids react with the amino groups to generate amide bonds, and the pH value of the functional powder can be adjusted after the reaction, without damaging the polyester; and no complex is formed between the iron ions and the amino groups, and the iron ions are doped into the zinc sulfide lattice, which is beneficial to the subsequent polyester polymerization, and the functional polyester obtained subsequently has a suitable molecular weight and a better antibacterial effect; and after the iron ion doping, the lattice defects of the zinc sulfide nano-material are increased, and the doping of trivalent iron ions increases the redox potential of the zinc sulfide, which is easily excited by light, heat, etc. to generate singlet oxygen, and decomposes organic harmful gases such as formaldehyde, acetaldehyde and propionaldehyde through oxidation.

[0037] The polyester fiber prepared by the preparation method of the polyester fiber of the present invention has dual anti-ultraviolet functions of shielding and converting ultraviolet rays, realizes the function of absorbing ultraviolet rays and emitting visible light through photon down-conversion, and the human body is beneficial to the absorption of vitamin D and calcium by absorbing visible light, which can compensate for the human body's demand for visible light; the polyester fiber has the function of decomposing formaldehyde, acetaldehyde and propionaldehyde after being woven into a fabric; the functional powder can play a role of catalytic polymerization in in-situ polymerization, reducing the use of catalysts; the mechanical properties of the polyester fiber reach the standards of ordinary fibers, and fully meet various weaving requirements; compared with the currently used antibacterial and anti-ultraviolet fibers, the cost is reduced by 70%, and the cost is lower than that of post-finishing processes; and pollution is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Attached Figure 1 is the excitation spectrum of the polyester fiber of Example 16; Attached Figure 2 : is the emission spectrum of the polyester fiber of Example 16 under different excitation wavelengths; Attached Figure 3 This is a fluorescence image of the polyester fiber of Example 16. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the illustrated embodiments.

[0040] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0041] Example 1

[0042] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 5%; 0.05% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.2% of the total mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 180°C within 30 minutes and maintained at this temperature for 24 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0043] Example 2

[0044] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 10%; 0.1% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.4% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 180°C within 30 minutes and maintained at this temperature for 24 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0045] Example 3

[0046] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 15%; 0.15% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.6% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 180°C within 30 minutes and maintained at this temperature for 24 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05:1, wherein the prepolymerization temperature is 180°C and the time is 60 min; the post-condensation temperature is 255°C and the time is 2 h; the final polymerization temperature is 275°C and the time is 2 h; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0047] Example 4

[0048] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 180°C within 30 minutes and maintained at this temperature for 24 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction concentration of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05:1, wherein the prepolymerization temperature is 180°C and the time is 60 min; the post-condensation temperature is 255°C and the time is 2 h; the final polymerization temperature is 275°C and the time is 2 h; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0049] Example 5

[0050] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) are dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine is 25%; 0.25% oxalic acid is added to the mixed solution, and the mixture is magnetically stirred for 10 minutes, and then 1% of the sum of the mass of zinc oxide and sulfur powder is added to the mixture. The mixture is stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for another 15 minutes; after sealing, the autoclave is heated to 180°C within 30 minutes and maintained at this temperature for 24 hours, and finally cooled naturally to room temperature; the precipitate is collected, washed with anhydrous ethanol and deionized water three times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction concentration of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0051] Example 6

[0052] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0053] Example 7

[0054] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 220°C within 30 minutes and maintained at this temperature for 12 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0055] Example 8

[0056] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 5%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0057] Example 9

[0058] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0059] Example 10

[0060] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 20%, and the grinding time is 6 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0061] Embodiment 11 (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0062] Example 12 (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 10%, and the grinding time is 10 h; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.1%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0063] Embodiment 13 (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.2%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0064] Embodiment 14 (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.4%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0065] Embodiment 15 (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur source in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the total mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes; after sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 0.8%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0066] Example 16 (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 min; the post-condensation temperature is 255°C and the time is 2 h; the final polymerization temperature is 275°C and the time is 2 h; the mass fraction of the functional powder in the polyester chips is 1.2%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0067] Embodiment 17 (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the sum of the mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 minutes; the post-condensation temperature is 255°C and the time is 2 hours; the final polymerization temperature is 275°C and the time is 2 hours; the mass fraction of the functional powder in the polyester chips is 1.6%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0068] Comparative Example 1 This example is different from Example 16 in that oxalic acid and ferric chloride hexahydrate are not added, as follows.

[0069] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; the mixture was stirred for 15 minutes, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for another 15 minutes; after sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water three times, and dried in a vacuum oven at 60°C for 6 hours to obtain functional powder;

[0070] (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization method: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional nano powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 min; the post-condensation temperature is 255°C and the time is 2 h; the final polymerization temperature is 275°C and the time is 2 h; the mass fraction of the functional powder in the polyester chips is 1.2%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain polyester fibers.

[0071] Comparative Example 2 This example is different from Example 16 in that no oxalic acid is added, as follows.

[0072] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) are dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine is 20%; then, hexahydrate chlorine compound (FeCl3·6H2O) is added to the mixture in a molar ratio of 0.8% of the sum of the mass of zinc oxide and sulfur powder, and the mixture is stirred for 15 minutes, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for another 15 minutes; after sealing, the autoclave is heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate is collected, washed with anhydrous ethanol and deionized water three times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization: Add the dispersed antibacterial and ultraviolet light absorbing and visible light emitting functional nanopowder ethylene glycol blend into ethylene glycol to form a mixture, and then carry out in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 min; the post-condensation temperature is 255°C and the time is 2 h; the final polymerization temperature is 275°C and the time is 2 h; the mass fraction of the functional powder in the polyester chips is 1.2%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain polyester fibers.

[0073] Comparative Example 3 This example is different from Example 16 in that no ferric chloride hexahydrate is added, as follows.

[0074] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in a mixed solvent of ethylenediamine and ethanolamine in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes, then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes; after sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water three times, and dried in a vacuum oven at 60°C for 6 hours to obtain functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 min; the post-condensation temperature is 255°C and the time is 2 h; the final polymerization temperature is 275°C and the time is 2 h; the mass fraction of the functional powder in the polyester chips is 1.2%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0075] Comparative Example 4 This example is different from Example 16 in that no ethylenediamine is added, as follows.

[0076] (1) Preparation of functional powder: zinc oxide (ZnO) and sulfur powder (S) were dissolved in an ethanolamine solvent in a molar ratio of 1:1, and the mass fraction of zinc oxide and sulfur powder in the mixed solvent of ethylenediamine and ethanolamine was 20%; 0.2% oxalic acid was added to the mixed solution, and the mixture was magnetically stirred for 10 minutes. Then, 0.8% of the total mass of zinc oxide and sulfur powder was added to the mixture. The mixture was stirred for 15 minutes and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene and stirred for 15 minutes. After sealing, the autoclave was heated to 200°C within 30 minutes and maintained at this temperature for 18 hours, and finally cooled naturally to room temperature; the precipitate was collected, washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum oven at 60°C for 6 hours to obtain iron-doped zinc sulfide functional powder; (2) Grinding and dispersing functional powders: The antibacterial and ultraviolet absorbing and visible light emitting functional powders prepared in step (1) are prepared into nanopowders by liquid grinding and dispersed in an ethylene glycol medium, and titanates are added as surface modifiers and dispersants to improve their dispersibility to obtain a blend, wherein the amount of titanates added is 1% of the mass of the functional powders prepared in step (1), the mass fraction of the functional powders prepared in step (1) in the ethylene glycol medium is 15%, and the grinding time is 8 hours; (3) Preparation of antibacterial and ultraviolet light absorbing and visible light emitting functional polyester by in-situ polymerization: adding the antibacterial and ultraviolet light absorbing and visible light emitting functional powder ethylene glycol blend dispersed in step (2) to ethylene glycol to form a mixture, and then in-situ polymerization with terephthalic acid at a molar ratio of 1.05-1, wherein the prepolymerization temperature is 180°C and the time is 60 min; the post-condensation temperature is 255°C and the time is 2 h; the final polymerization temperature is 275°C and the time is 2 h; the mass fraction of the functional powder in the polyester chips is 1.2%; (4) Spinning: After drying, the polyester chips with antibacterial and ultraviolet light absorbing and visible light emitting functions are fed into the feeder of the spinning machine for melt spinning. The spinning temperature is 285°C, the spinning speed is 2800m / min, and the initial pressure of the spinning assembly is 9MPa to obtain antibacterial and ultraviolet light absorbing and visible light emitting polyester fibers.

[0077] Performance Testing The particle size of the functional powder in step (1) of Examples 1-17 and Comparative Examples 1-4 was tested by a laser particle size analyzer. The antibacterial effect of the polyester fibers of Examples 1-17 and Comparative Examples 1-4 on Escherichia coli, Staphylococcus aureus and white / light-colored Streptococcus was tested, and the effect of absorbing ultraviolet light and emitting visible light was tested. The woven fabric was tested for formaldehyde removal, wherein the antibacterial and ultraviolet absorption and visible light emission effects of the prepared fibers were tested according to the test standard of GB / T20944.3-2008, and the formaldehyde test was detected according to JC / T1004-2008.

[0078] The particle sizes of the functional powders and the absorption spectrum data and emission spectrum data of the polyester fibers of Examples 1-17 and Comparative Examples 1-4 are shown in Table 1 below:

[0079] In Examples 1-5, the mass fraction of zinc oxide and sulfur powder in Example 4 dissolved in the mixed solvent of ethylenediamine and ethanolamine is 20%, and the obtained nano-functional powder has the smallest particle size and the best effect.

[0080] In Example 7, when the reaction temperature of step (1) is too high, the reaction speed is accelerated, and the particle size of the functional powder produced is increased. Compared with Example 6, the antibacterial effect is reduced. The optimal reaction temperature is 200°C and the reaction time is 18h.

[0081] In Example 8, compared with Example 7, lowering the grinding concentration (the mass fraction of the functional powder prepared in step (1) dispersed in the ethylene glycol medium by liquid grinding) is beneficial to reducing the powder particle size. It is preferred to use a relatively high concentration for grinding, which has high production efficiency.

[0082] In Example 10, compared with Example 9, the grinding concentration (the mass fraction of the functional powder prepared in step (1) dispersed in the ethylene glycol medium by liquid grinding) was increased, but the powder particle size increased and the antibacterial and anti-ultraviolet properties decreased. Therefore, the grinding concentration was set at 15% as the best.

[0083] In Example 12, compared with Example 11, the grinding time of step (2) was increased, but the particle size did not change, indicating that the particle size had reached the minimum at this time. Considering the work efficiency, the grinding time was set to 8 hours as the best.

[0084] The woven fabric of Example 16 was tested for formaldehyde removal according to JC / T1004-2008, and the formaldehyde removal efficiency was 87%. After iron ion doping, the lattice defects of the zinc sulfide nanomaterial are increased, and the doping of trivalent iron ions increases the redox potential of zinc sulfide, which is easily excited by light and heat to produce singlet oxygen, and decompose organic harmful gases such as formaldehyde, acetaldehyde and propionaldehyde through oxidation.

[0085] In Example 17, the content of nano-functional powder in the polyester chips continued to increase, the antibacterial efficiency remained basically unchanged, the anti-ultraviolet performance did not increase significantly, and the increase of inorganic functional powder would affect the spinning efficiency and fiber mechanical properties, and increase the fiber cost. Therefore, the mass fraction of functional powder in the polyester chips is preferably 1.2%.

[0086] The molecular weight of the functional polyester obtained in step (2) of comparative example 1 was 21,000, which was relatively low and caused floating fibers to form during spinning.

[0087] In comparative example 2, since the pH of the system was not adjusted, a complex was formed between the iron ions and the amino groups, resulting in only a portion of the iron ions participating in the zinc sulfide doping, which affected both the antibacterial effect and the polyester polymerization, and the molecular weight was low. The molecular weight of the functional polyester obtained in step (2) was 20,000, and the molecular weight of the polyester was low, resulting in floating silk phenomenon during spinning.

[0088] The formaldehyde removal efficiency of the fabric woven in Comparative Example 2 is lower than that of the fabric woven in Example 16. Compared with Examples 1-12, the mass fraction of the functional powder in the polyester chips of Comparative Example 2 is relatively high, and the formaldehyde removal efficiency is relatively high.

[0089] In Comparative Example 3, oxalic acid is added, and the oxalic acid reacts with the amino groups on the surface of the functional powder, causing its antibacterial performance to decrease; however, the addition of oxalic acid prevents agglomeration, and the particle size of the functional powder is reduced. The anti-ultraviolet performance of Comparative Example 3 is better than that of Comparative Example 1.

[0090] In addition, the reason why the polyesters in Comparative Examples 1 and 3 have no formaldehyde removal efficiency is that: no ferric chloride hexahydrate is added in Comparative Examples 1 and 3, and the iron-doped zinc sulfide functional powder has a photocatalytic degradation function, and thus has a formaldehyde removal function. Zinc sulfide is a quantum dot and has a light conversion function, which can absorb ultraviolet rays and convert them into visible light. After being doped with iron, the lattice of the zinc sulfide nanopowder has defects to form holes, and at this time, it can absorb ultraviolet rays and visible light to react with oxygen in the air to form free radicals. Oxygen free radicals have an oxidizing function and can decompose formaldehyde in the air, thereby giving the iron-doped zinc sulfide the formaldehyde removal function. Without iron doping, zinc sulfide has no defects, and no oxygen free radicals will be generated. Therefore, the polyesters in Comparative Examples 1 and 3 do not have the formaldehyde removal function.

[0091] For the woven fabric of Example 16, see Figure 1 and Figure 2 , has maximum absorption and emission under ultraviolet 360nm excitation, and the wavelength of emitted visible light is 450nm. Figure 1 and Figure 2 The polyester fiber of the present invention absorbs ultraviolet light and emits visible light, the ultraviolet light range is 200-400nm, and the visible light range is 400-800nm. Figure 3 The polyester fiber of the present invention belongs to fluorescent material, which is instantaneous, emitting visible light when there is excitation light, and not emitting visible light when there is no excitation light, without delay.

[0092] The preparation method of the polyester fiber of the present invention comprises the following steps: firstly obtaining an iron-doped zinc sulfide nano material as a functional powder, and then modifying the nano material through chemical surface modification to improve the compatibility with resin, so as to have the performance of low addition amount and good effect; then polymerizing through an in-situ polymerization process, and finally obtaining an antibacterial polyester fiber capable of absorbing ultraviolet rays and emitting visible light through a melt spinning process, wherein the fiber diameter can be ultrafine, the fiber can be made into a light color, and the polyester fiber has the functions of long-term antibacterial and absorbing ultraviolet rays and emitting visible light; different from the traditional anti-ultraviolet fiber, the polyester fiber has the dual anti-ultraviolet functions of shielding and converting ultraviolet rays, realizes the functions of absorbing and emitting visible light through photon down-conversion, can compensate for the human body's demand for visible light, has mechanical properties reaching the standards of ordinary fibers, fully meets various weaving requirements, has a lower cost than a post-finishing process, and the functional powder can play a role of catalytic polymerization in the in-situ polymerization, thereby reducing the use of catalysts, and compared with the currently used antibacterial and anti-ultraviolet fibers, the cost is reduced by 70%, pollution is reduced, the export of textiles can be expanded, and the added value of textiles can be increased.

[0093] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing polyester fiber, characterized in that: include: (1) firstly adding zinc oxide and a sulfur source into a mixed solvent of ethylenediamine and ethanolamine, and then adding an organic acid and an iron-containing compound to react to obtain a functional powder, wherein the iron in the iron-containing compound is trivalent iron, and the reaction temperature is controlled to be 180-220°C during the reaction; (2) The functional powder of step (1) is mixed with polyester raw material to carry out in-situ polymerization reaction to obtain functional polyester chips, which are then melt-spun to obtain polyester fibers.

2. The method for preparing polyester fiber according to claim 1, characterized in that: In step (1), the iron-containing compound is a combination of one or more selected from ferric chloride and ferric sulfate.

3. The method for preparing polyester fiber according to claim 1, characterized in that: In step (1), the amount of the iron-containing compound added is 0.2-2% of the sum of the mass of the zinc oxide and the sulfur source.

4. The method for preparing polyester fiber according to claim 1, characterized in that: In step (1), the organic acid is a combination of one or more selected from oxalic acid and acetic acid.

5. The method for preparing polyester fiber according to claim 1, characterized in that: In step (1), the amount of organic acid added is 0.05-0.2% of the sum of the mass of zinc oxide and sulfur source.

6. The method for preparing polyester fiber according to claim 1, characterized in that: In step (1), the mass ratio of ethylenediamine to ethanolamine is (1:2)-(2:1).

7. The method for preparing polyester fiber according to claim 1, characterized in that: In step (1), the molar ratio of the zinc oxide to the sulfur source is (1:1.1)-(1.1:1); and\or, the mass fraction of the zinc oxide and the sulfur source dissolved in the mixed solvent of ethylenediamine and ethanolamine is 5-25%.

8. The method for preparing polyester fiber according to claim 1, characterized in that: In step (2), the functional powder of step (1) is first dispersed in a polyol medium, and then a surface modifier is added to obtain a blend. The blend is then in-situ polymerized with a polyol and a polyacid to obtain a functional polyester chip, wherein the mass fraction of the functional powder in the polyester chip is 0.1%-2%.

9. The method for preparing polyester fiber according to claim 8, characterized in that: In step (2), the blend is added to a polyol and then in-situ polymerized with a polyacid, wherein the molar ratio of the polyol mixed with the blend to the polyacid is (1-1.2):1; and\or, in step (2), the polymerization is divided into prepolymerization, post-condensation polymerization, and final polymerization, the prepolymerization temperature is 170-200°C, and the time is 40-80min; the post-condensation temperature is 230-270°C, and the time is 1-3h; the final polymerization temperature is 260-290°C, and the time is 1-4h.

10. A method for preparing a catalyst, characterized in that: include: Firstly, zinc oxide and a sulfur source are dissolved in a mixed solvent of ethylenediamine and ethanolamine, and then an organic acid and an iron-containing compound are added to react to obtain a functional powder, wherein the iron in the iron-containing compound is trivalent iron, and the reaction temperature is controlled to be 180-220°C during the reaction.

Citation Information

Patent Citations

  • Method for preparing spiauterite ZnS fine nanorod with solvothermal method

    CN102249289A

  • Antibacterial nano fiber and preparation method thereof

    CN111455497A

  • Preparation method and application of polyester master batch with formaldehyde degradation function

    CN118206851A

  • Process for the production of polyethylene terephthalate copolyester, copolyester obtained thereby and its use and catalyst useful in the process

    CN1961022A